Diffusion tensor imaging of white matter integrity in relation to smoking index and exacerbations in severe chronic obstructive pulmonary disease - Eman Mohamed Helmy (The Egyptian Journal of Radiology and Nuclear Medicine, 2019)
Abstract Background Diffusion tensor imaging (DTI) is a non-invasive MR modality that provides an evaluation of brain tissue microstructure and architecture in vivo. We aimed to assess the diagnostic value of DTI parameters in evaluating cerebral white matter integrity in patients of severe chronic obstructive pulmonary disease (COPD) and correlate these parameters with smoking index (SI) and the number of exacerbations in the last year. This prospective study included 30 COPD male past smoker patients and 15 age- and sex-matched nonsmoker controls. Staging of COPD, SI and number of exacerbations in the last year were obtained. Routine brain MRI and DTI were done in all subjects. The selected white matter tracts’ fractional anisotropy (FA), and mean diffusivity (MD) were calculated in the region of interest in axial slices. Results The mean FA and MD values of all selected white matter tracts showed a high significant difference (p < 0.001) between patients and control group. The correlation between FA, SI and exacerbation frequency was not significant in the majority of white matter tracts (p > 0.05). The correlation between MD, SI and exacerbation frequency was significant for the majority of tracts (p < 0.05). Conclusion DTI metrics are valuable non-invasive tools in evaluating the white matter abnormalities in COPD patients. Smoking index and frequency of exacerbations have possible relation to extra-pulmonary cerebral manifestations of COPD.